PENGARUH RETURN ON ASSETS, DEBT TO EQUITY RATIO, DAN EARNING PER SHARE TERHADAP NILAI PERUSAHAAN (Studi Kasus Pada Perusahaan Food and Beverages Yang Terdaftar Di BEI Periode 2009-2011) - Winur Haryati; Sri Ayem (Jurnal Akuntansi, 2014)
This study aims to determine whether the return on assets , debt to equity ratio , and earnings per share have an influence on the value of the company at the company's food and beverages . The research data collection using polling , so the amount of data to be processed is the product of the number of samples with the company during the period of observation period , which is 14 times the company 3 years , so that the resulting sample of 42 . Data analysis was performed using linear regression analysis using SPSS for windows 16. Simultaneous testing results show that the return on assets ( X1 ) , debt to equity ratio ( X2 ) , and earnings per share ( X3 ) all positive and significant effect on firm value , while the partial test results show that of the three independent variables , namely , return on assets , debt to equity ratio , earnings per share and there are two variables are positive and significant effect on firm value is variable return on assets and earnings per share , while the debt to equity ratio variable had no significant effect on firm value. Keywords: Return on assets, debt to equity ratio, earnings per share